Comparative Ubiquitome Analysis Reveals Deubiquitinating Effects Induced by Wolbachia Infection in Drosophila melanogaster. - Zong, Q.; Mao, B.; Zhang, H.B.; Wang, B.; Yu, W.J.; Wang, Z.W.; Wang, Y.F. (International journal of molecular sciences, 2022)
The endosymbiotic Wolbachia bacteria frequently cause cytoplasmic incompatibility (CI) in their insect hosts, where Wolbachia-infected males cross with uninfected females, leading to no or fewer progenies, indicating a paternal modification by Wolbachia. Recent studies have identified a Wolbachia protein, CidB, containing a DUB (deubiquitylating enzyme) domain, which can be loaded into host sperm nuclei and involved in CI, though the DUB activity is not necessary for CI in Drosophila melanogaster. To investigate whether and how Wolbachia affect protein ubiquitination in testes of male hosts and are thus involved in male fertility, we compared the protein and ubiquitinated protein expressions in D. melanogaster testes with and without Wolbachia. A total of 643 differentially expressed proteins (DEPs) and 309 differentially expressed ubiquitinated proteins (DEUPs) were identified to have at least a 1.5-fold change with a p-value of <0.05. Many DEPs were enriched in metabolic pathway, ribosome, RNA transport, and post-translational protein modification pathways. Many DEUPs were involved in metabolism, ribosome, and proteasome pathways. Notably, 98.1% DEUPs were downregulated in the presence of Wolbachia. Four genes coding for DEUPs in ubiquitin proteasome pathways were knocked down, respectively, in Wolbachia-free fly testes. Among them, Rpn6 and Rpn7 knockdown caused male sterility, with no mature sperm in seminal vesicles. These results reveal deubiquitylating effects induced by Wolbachia infection, suggesting that Wolbachia can widely deubiquitinate proteins that have crucial functions in male fertility of their hosts, but are not involved in CI. Our data provide new insights into the regulatory mechanisms of endosymbiont/host interactions and male fertility.